Islamic Child Personality Education Concepts By Al-Ghazali - Rifki El-Faizal; Mulya (MAQOLAT: Journal of Islamic Studies, 2023)
This research is intended to answer the following problems: 1) What is the concept of personality education according to Al-Ghazali in the book Ayyuhal Walad ? 2) How is it relevant to the concept of child personality education according to Al-Ghazali in the Ayyuhal Walad book with education in Indonesia? This research is a literature research qualitative category, with the data source in the form of a book by Imam Al-Ghazali. Data collection is done through observation of primary and secondary data sources. Data analysis was carried out by giving meaning to the data that was collected and from that meaning a conclusion was drawn. The results of this study indicate that the Ayyuhal Walad book contains personality education for children, namely: 1) Forming an obedient and pious person to Allah SWT. 2) Forming a trusting personality 3) Forming a sincere personality 4) Forming a person who is istiqomah 5) Forming a person who has tolerance and a social spirit 6) Forming a person who respects the teacher. In addition, the concept of personality education in the Ayyuhal Walad book is relevant to education in Indonesia, such as the goals of national education and character and exemplary education in education.